Efektivitas Dan Efisiensi Sistem Inventaris Laboratoium Online - riswanto riswanto (Jurnal Pendidikan Fisika, 2019)
The era of disruptive innovation globalization is marked by the digitalization of all aspects of life, including education-based on big data. The laboratory is a minimum standard that must be held by education providers, and the goal is to support science learning activities. Laboratory systems that have been developed online need to be reviewed for their effectiveness and efficiency values. The research method was carried out by data triangulation and snowball techniques in the form of quantitative data and qualitative data. The results obtained that the effectiveness of the online laboratory system provides convenience in carrying out practical activities and ease of communication for laboratory users. As efficient as the online physics laboratory inventory system is, it takes six times faster to utilize an online laboratory inventory system when compared to a manual mode.